Contributions to Improve Accessibility and Usability of Academic Journal Management Systems. Case Study: OJS - Arias-Flores, Hugo (2020)
Assistive technologies have allowed people with disabilities to overcome many barriers. For instance, people with visual disabilities are able to access information on the Web by using screen readers and generating different actions in their navigation, which would not be possible without assistive technology. The generation of accessible resources and understanding user behavior from the journal editorial process point of view have created changes in the editorial process itself, from the reception to the publication of the articles. In this digital age, in which information has become global and open to a diverse population, resources should be accessible. Unfortunately, this is not usually the case. Resources must be made accessible to people with different conditions, including visual and hearing impairments. The goal of this study is to identify the challenges faced by a person with a visual disability during the editorial process of journals on the Open Journal Systems (OJS) platform. Such challenges include understanding the layout of the elements and controls on the platform interface, creating HTML versions of academic articles, configuring journal websites, and so on. The aim of addressing these challenges is to create accessible resources that can be used by all readers of OJS journals regardless of their conditions. The information presented in this study was collected over six months, and a descriptive analysis was performed. It can be noted that some accessible resources have already been implemented, such as the presentation of academic articles in MP3 format (which can be downloaded or reproduced online) and the publication of HTML versions of complete articles with navigation levels. There is also a video resource in which authors expose their research, and the articles themselves are presented in an accessible PDF format (which respects levels of accessibility that allow greater reading enjoyment for users with vision impairments). These contributions allow people with visual disabilities to better integrate into editorial teams of scientific journals. Work continues so that the resources published on the OJS platform can reach readers with disabilities at greater regional and global levels. © 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.